Synergistic effect of photodynamic therapy and cisplatin: a novel approach for cervical cancer - Freitas, Laura Marise de [UNESP]; Soares, Christiane Pienna [UNESP]; Fontana, Carla Raquel [UNESP] (Elsevier B.V., 2014)
Cervical cancer is a neoplasia primarily caused by Human papillomavirus (HPV) infection. Current treatment modalities involve cisplatin, a potent chemotherapeutic agent with severe adverse effects. Photodynamic therapy (PDT) is a promising modality for the treatment of cancer and infections, which has been associated with innovative therapeutic approaches, especially for the treatment of neoplasias. This study aimed to investigate the anticancer potential of PDT mediated by methylene blue (MB) or Photogem (PG) individually and combined with cisplatin in vitro. SiHa, C-33 A and HaCaT cells were incubated with MB, PG and/or cisplatin and received no further treatment or were irradiated with a 630 or a 660 nm LED light source at energy densities varying according to the photosensitizer (PS). The MTT assay was employed to assess cell viability. Both PS were effective in reducing cell viability with the cytotoxicity being dependent on the light dose. When compared to PDT groups, cisplatin was less effective. The cell viability of the combined therapy groups was significantly lower compared to monotherapies. The sequence of treatments (PDT + cisplatin/cisplatin + PDT) was important and had different results when varying the PS, but combination therapy resulted in an enhanced anticancer effect regardless of treatment protocol. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Photodynamic therapy; Cisplatin; Cervical cancer; Combined therapy